Granulocytic Sarcoma of the Uterus: A Rare Presentation of Extramedullary Relapse of AML and Importance of MRI - Murat Ucar; Melike Guryildirim (Case Reports in Radiology)
Granulocytic sarcoma (GS) is a solid tumor that is the extramedullary presentation of acute myelogenous leukemia, other myeloproliferative disorders, or myelodysplastic syndromes. Less commonly, it also may arise as an isolated mass. In this report, we describe a 23-year-old female patient, with a GS in the uterus and we stress the value of diffusion weighted imaging for the evaluation of uterine neoplasms. To our knowledge, our case is the first in the literature to report diffusion weighted imaging (DWI) findings of GS.